The street as a performing stage and as a vocation: some reflections on street theatre in Buenos Aires (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
In this article we want to introduce some reflection on colective street theatre in the city of Buenos Aires in the last years. We will draw some theorical and methodological lines to approach the concept of popular in the theatrical area, attending to cultural studies, theatrical theories and anthropology, and analyze in a second step some experiences narrated by actors of street theatre. We will also introduce briefly the story of a group which is recognized as a reference of street theatre in Buenos Aires: La Runfla, founded in 1991, who’s political and artistical activities take place in Parque Avellaneda and contributed to the revaluation of this public space.
Keywords: Street theatre; Public space; Popular